Computational algorithms and the effectiveness of budget rules - Teixeira Neto, Francisco Edilson (2021)
The relationship between financial rules and technology, for the purpose of maximizing the effectiveness of budget law standards, i.e., contribution to the fulfillment of such rules, provides meditations on the interactions between principles and rules with the development and application of technologies. In this perspective of reflection, the investigation of possible contribution of technologies, such as algorithms, machine learning and artificial neural networks, to optimize the field of effectiveness of budget standards, is victorious regarding the possibility of study and understanding, mainly because we are experiencing the fourth industrial revolution. This research, therefore, makes itself available to analyze, in a critical way, the question marks worthy of further discussion.